Religious Moderation Strengthening Strategies through the Formulation of Anti-violence Culture at Pesantren - Muhammad Ma'aliyal Umur; Ulfa Maskanah; Ceni Amalia Ayu Lestari; Nur Ali; Bakhruddin Fanani (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2025)
This research aims to analyze the institute's policy for strengthening a culture of religious moderation against violence. The research focuses on the process of formulating policies and implementing anti-violent religious moderation values. This study uses a qualitative case study approach. The data were collected through in-depth interviews with pesantren leaders, two ustadhs, and Islamic students (santri), as well as document data. The results of the study show that policy formulation to strengthen religious moderation is carried out in a participatory manner through deliberation led by the kiai as the holder of the highest authority. The value of anti-violence is the primary foundation in the formulation of institutional policies. Policy implementation is carried out through the example of Kiai, the study of classical texts focused on manners and character development that reject physical punishment, and santri's social activities that strengthen harmonious interactions with the community. This study concludes that transformative and contextual kiai leadership is the main factor in the success of internalizing the value of anti-violent religious moderation in pesantren. This finding contributes to the understanding that pesantren, as socio-religious entities, play an active role in building a peaceful religious life.